ESG disclosure as a signaling mechanism linking green capabilities to competitive advantage - M. F. Arrozi Adhikara; Fredy Rizaldi; Sugiyanto Sugiyanto; Agung Mulyo Widodo (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2025)
This study examines whether Environmental, Social, and Governance (ESG) disclosure serves as a signaling mechanism that links green organizational capabilities to competitive advantage. Survey data were collected from 183 managers of agricultural manufacturing firms listed on the Indonesia Stock Exchange and analysed using Structural Equation Modeling. The study focuses on the relationships among Environmental Consciousness (EC), Green Intellectual Capital (GIC), ESG disclosure, and Green Competitive Advantage (GCA). The findings show that EC strengthens GIC, which then improves the quality of ESG disclosure. The results also indicate that EC and GIC affect GCA only through ESG disclosure, rather than through environmental initiatives alone. This suggests that green capabilities influence competitive outcomes mainly when they are communicated clearly to external stakeholders. Disclosure practices are often linked to better reputation and cost efficiency, but they seem to play a smaller role in product differentiation. Over time, many firms strengthen the connection between green strategies and ESG reporting by making gradual investments in reporting activities and innovation, which can improve disclosure quality, lower concerns about greenwashing, and help support efficiency.